Management of axillary burn contracture: A summary of 67 cases - L. Ndiaye; A.A. Sankale; Aï Ndiaye; M.L. Foba; N.F. Coulibaly (Elsevier, 2018)
The scapulo-humeral joint has the greatest range of motion of all joints. Axillary contractures, mostly sequela of trunk burn, are sometimes cause of important hindrances in daily activities. Once installed, their treatment are essentially surgical. The purpose of this study was to describe epidemiologic and clinical profile and to evaluate the therapeutic results. We carried out a review from January 2001 to December 2016. Sixty-seven patients with all post-burn axillary sequelae were included. The Kurtzman-Stern's classification was used to describe the type of contracture. Surgical procedure consisted of releasing scar and covering the loss of substance by local plasty, skin grafting or loco-regional flap. The average age was 21 years [2-76 years] with a sex ratio (M/F) = 0.5. Post-burn contracture was following burn flame in 43 cases (64%) and hot fluid in 18 cases (27%). The mean duration of contracture was 3.3 years [1 month-20 years]. Type 1 and 2 were noted in 22 cases (33%), type 3 in 45 cases (67%). The deficit of abduction varied between 30° and 110°. Thirty-eight patients have been operated. Twenty-six patients underwent local plasty, 11 patients was treated by skin graft and one patient was treated by para-scapular flap. The complications were dominated by minor flap necrosis and skin graft loss in 9 cases (24%). After an average follow-up of 4 years, functional results were considered as satisfactory in more than 80% of cases.Management of post-burn axillary contracture flap and skin graft gives good results despite the minor complications related to peri axillary scar and difficulties of post operative immobilization of the shoulder. Early surgery and physiotherapy are important to achieve better results by avoiding ligament and capsular retractions. Keywords: Burn, Contracture, Axillary, Surgery, Physiotherapy